جود الحياة وعلاقتها بالدافعية للتعلم لدى الطالب - مسعودي مريم; بالطاهر النوي (University of Eloued جامعة الوادي, 2024)
الملخص: هدفت الدراسة إلى الكشف عن العلاقة بين مستوى جودة الحياة والدافعية للتعلم والتعرف على الفروق في مستوى الدافعية للتعلم لذوي جودة الحياة المرتفعة تبعا لمتغيرات: التخصص الدراسي، المستوى التعليمي وذلك باستخدام المنهج الوصفي ؛ وتكونت العينة من( 135) طالبا وطالبة يدرسون بجامعة الوادي تم اختيارهم بالطريقة العشوائية الطبقية ذات التوزيع المتناسب وتبنى الباحث مقياسين هما ؛ مقياس جودة الحياة ومقياس الدافعية للتعلم لدى طلبة الجامعة، وتم التوصل إلى أنه توجد علاقة ارتباطية دالة إحصائيا بين جودة الحياة والدافعية للتعلم، وأنه توجد فروق دالة إحصائيا في مستوى الدافعية للتعلم للطلبة الجامعة ذوي مستوى جودة الحياة المرتفعة تعزي لمتغير التخصص وعدم وجود فرق دالة إحصائيا في مستوى الدافعية للتعلم للطلبة ذوي مستوى جودة الحياة المرتفعة يعزى لمتغير مستواهم التعليمي. Abstract : : The study aimed to investigate the relationship between the quality of life and motivation for learning, and to identify differences in the level of motivation for learning among individuals with high quality of life based on variables such as academic specialization and educational level, using a descriptive approach. The sample consisted of 135 male and female students studying at Al-Wadi University, who were selected using stratified random sampling. The researcher adopted two scales: the quality of life scale and the motivation for learning scale among university students. The findings revealed a statistically significant correlation between the quality of life and motivation for learning. Moreover, there were statistically significant differences in the level of motivation for learning among university students with high quality of life, which can be attributed to the variable of academic specialization. However, there were no statistically significant differences in the level of motivation for learning among students with high quality of life, which can be attributed to their educational level.
دراسة ميدانية بجامعة الوادي
Keywords: جودة الحياة; الدافعية للتعلم; طلبة الجامعة; quality of life; motivation for learning; university students